Pattern of Penile Cancers in Kano - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:The prevalence of penile cancer differs from region to region across the globe. The highest prevalence was reported in some parts of the developing countries in South America and Africa. However, its epidemiology in our population is unknown. Our study, therefore, aimed to describe the frequency, the age of presentation, and the histological spectrum of penile cancers seen in Kano, Northern Nigeria.Materials and Methods:This study was an 18-year retrospective appraisal from 1998 to 2015 of all the histological diagnosed penile cancers recorded at the Aminu Kano Teaching Hospital, Kano, Nigeria. Where necessary, a new slide was reprocessed from tissue block for re-evaluation.Results:Six penile cancers were diagnosed during the study period. Patient’s age ranged from 50 to 75 years (mean 59.70 years). Three patients (50%) were in the 50–59 years age group. All the six cases were squamous cell carcinomas, five (83.3%) were well differentiated and one (16.7%) was poorly differentiated.Conclusion:This review affirmed the low prevalence of penile cancer in our population which may not be detached from the common tradition of circumcision in our populace.